Transplantation impacts on the oral microbiome of kidney recipients and donors - Campbell, Paul M.; Willmott, Thomas; Humphreys, Gavin J.; Piscoran, Oana; Chea, Houda; Summers, Angela M.; Konkel, Joanne E.; Knight, Christopher G.; Augustine, Titus; McBain, Andrew J. (Frontiers in Microbiomes, 2023)
Introduction Chronic kidney disease (CKD) may affect the human microbiome via increased concentrations of uremic toxins such as urea and creatinine. Methods We have profiled the oral microbiota in patients with CKD before and one week after kidney transplantation. Living kidney donors were also longitudinally tracked over a similar period, allowing direct comparison between a group undergoing transplant surgery alone (donors) (n=13) and a group additionally undergoing the introduction of immunosuppressive agents and the resolution of CKD (recipients) (n=45). Results Transplantation was associated with a similar pattern of decreasing alpha diversity in the oral microbiome in recipients and donors via Kruskal-Wallis testing, within one week of transplantation. Amplicon sequence variants (ASVs) associated with Haemophilus parainfluenzae, Aggregatibacteria segnis, Peptostreptococcus and Actinobacillus were significantly decreased in recipients within a week of transplantation. Discussion A reduction in ASVs in these genera could influence the risk of bacterial endocarditis, a rare but high-mortality kidney transplantation complication. A range of factors may drive the observed changes in oral microbiome including both factors associated with surgery itself and the decreases in salivary urea, administration of macrolide antibiotic immunosuppressants, and disruption to immune function that characterise kidney transplant.